The (Non) Implementation of the Marketing Concept Within the Croatian Educational System with Special Reference to Higher Educational Institutions - Miletić, Josip; Bosna, Jurica (Oeconomica Jadertina, 2017)
This is a relevant subject due to the high level of unemployment and the associated structural unemployment present in Croatia. The authors propose the introduction of the marketing concept in the Croatian educational system in order to stimulate the overcoming of the gap between the unemployed working force and the job market. The paper presents the educational system and its elements by explaining the specifics of marketing in education, provides guidelines for the managing of the educational system based on the marketing principle, and indicates the consequences of (non)implementation of the marketing concept within the Croatian educational system. The introduction of the marketing principle in the education system, together with the application of other important structural reforms, should improve the currently weak labor market situation.